Molecular Encapsulation of Herbicide Terbuthylazine in Native and Modified β-Cyclodextrin - E. Manuela Garrido; Daniela Rodrigues; Nuno Milhazes; Fernanda Borges; Jorge Garrido (Journal of Chemistry)
The herbicide terbuthylazine (TBA) is widely used for preemergence or postemergence control of many grass and broadleaf weeds and has, besides other issues, a poor aqueous solubility profile that results in reduced bioavailability. Cyclodextrins and modified cyclodextrins were considered, among other substances, appropriate agents for improving pesticide water solubility. Therefore, the inclusion complex formation of terbuthylazine with β-cyclodextrin (β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD) was studied to attain its aqueous solubility enhancement. Their characterization was accomplished with different analytical techniques, namely, by UV-Vis, DSC, FTIR, and 1H NMR. From the analysis of the complexation performance of the herbicide it was concluded that the interaction of terbuthylazine with CDs leads to the formation of inclusion complexes with a stoichiometry of 1 : 1. The association constants of the TBA/β-CD and TBA/HP-β-CD complexes were determined by UV. The mean values obtained for the stability constants are 460.4 ± 26.5 and 532.1 ± 27.6 to TBA/β-CD and TBA/HP-β-CD, respectively. 1H NMR data corroborate the formation of the TBA/β-CD and TBA/HP-β-CD complexes synthesized by the kneading method. A formulation incorporating TBA cyclodextrin complexes might lead to an improvement in terbuthylazine bioavailability. The development of TBA-CD formulations may be interesting since it would enable, through their inclusion into the hydrophobic cavity of CDs, enhancement of solubility, bioavailability, and stability of the herbicide.